A Competitive Study Using UV and Ozone with H2O2 in Treatment of Oily Wastewater (Baghdad Science Journal, 2020)
In this study, ultraviolet (UV), ozone techniques with hydrogen peroxide oxidant were used to treat the wastewater which is produced from South Baghdad Power Station using lab-scale system. From UV-H2O2 experiments, it was shown that the optimum exposure time was 80 min. At this time, the highest removal percentages of oil, COD, and TOC were 84.69 %, 56.33 % and 50 % respectively. Effect of pH on the contaminants removing was studied in the range of (2-12). The best oil, COD, and TOC removal percentages (69.38 %, 70 % and 52 %) using H2O2/UV were at pH=12. H2O2/ozone experiments exhibited better performance compared to the H2O2/UV experiments. The results showed that 20 min was the best exposure time with removal percentages of 89.79 %, 83.33 % and 70% for oil, COD and TOC, respectively, and the optimum value of pH was at pH=8, where the pollutants removal percentages (i.e. 74.48 %, 80 % and 73.33 % respectively for the same previous pollutants). H2O2/ozone experiments showed better removal efficiency than the H2O2/UV experiments.